Type the title of your paper here Effect of the focused light from the xenon arc lamp on the surface tension of the molten enamel; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Aleutdinov A. D. Alexander Dmitrievich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Mylnikova T. S. Tatyana Stepanovna; Aleutdinov K. A. (2016, 2016)
Title screen